MRV Expert Workshop - Kenya Experience - Kibor, Benjamin T. (2018)
Expert workshop on Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps The Hauge, July 17-18, 2018 Session 2 - Kenya